1997
DOI: 10.1523/jneurosci.17-02-00635.1997
|View full text |Cite
|
Sign up to set email alerts
|

The Type 1 Inositol 1,4,5-Trisphosphate Receptor Gene Is Altered in theopisthotonosMouse

Abstract: The opisthotonos (opt) mutation arose spontaneously in a C57BL/Ks-db2J colony and is the only known, naturally occurring allele of opt. This mutant mouse was first identified based on its ataxic and convulsive phenotype. Genetic and molecular data presented here demonstrate that the type 1 inositol 1,4,5-trisphosphate receptor (IP3R1) protein, which serves as an IP3-gated channel to release calcium from intracellular stores, is altered in the opt mutant. A genomic deletion in the IP3R1 gene removes two exons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 39 publications
7
87
0
Order By: Relevance
“…These mutant mice display some features of an ataxic and convulsive phenotype. Genetic data showed that the IP3R1 gene is modified in the opt mice [52]. A partial deletion of IP3R1 removes two exons but does not interrupt the translational reading frame.…”
Section: Mutations In the Ip3r1 Gene And Ataxiasmentioning
confidence: 99%
“…These mutant mice display some features of an ataxic and convulsive phenotype. Genetic data showed that the IP3R1 gene is modified in the opt mice [52]. A partial deletion of IP3R1 removes two exons but does not interrupt the translational reading frame.…”
Section: Mutations In the Ip3r1 Gene And Ataxiasmentioning
confidence: 99%
“…Several skeletal-muscle pathologies such as malignant hyperthermia, porcine stress syndrome, central-core disease, can be caused by mutations in ryanodine receptors (Missiaen et al, 2000). Brain InsP3Rs have been hypothesized to contribute to the pathology of episthotonos in mice (Street et al, 1997). Disturbance in InsP3R and RyR appears to be involved in neurodegenerative diseases such as Alzheimer's disease (Mattson and Chan, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inositol 1,4,5-trisphosphate receptor type 1 (IP3R1) intracellular Ca 2+ release channels, which localize to intracellular ER Ca 2+ stores, have been associated with seizures in mice (Street et al, 1997). However, a mechanistic relationship between dysfunction of intracellular Ca 2+ release channels and seizures has not been established.…”
Section: Ryanodine Receptor Mutations Cause Generalized Seizuresmentioning
confidence: 99%
“…However, a mechanistic relationship between dysfunction of intracellular Ca 2+ release channels and seizures has not been established. Ca 2+ is an important neuronal signaling molecule and intracellular Ca 2+ release channels are an important source including IP3R1-3 isoforms (Mignery et al, 1989;Street et al, 1997) and the related ryanodine receptor isoforms (RyR1-3) (Henzi & MacDermott, 1992;Kostyuk & Verkhratsky, 1994). Interestingly, mutation carriers with RyR2 mutations have been shown to exhibit syncope, seizures and cardiac arrhythmias (Postma et al, 2005).…”
Section: Ryanodine Receptor Mutations Cause Generalized Seizuresmentioning
confidence: 99%